PEMANFAATAN DATABASE ONLINE EBSCO BAGI PEMUSTAKA - Delvia Gustia Ramayanda (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2023)
This research was conducted to determine the use of the Ebsco online database subscribed by the UPT Library of Universitas Negeri Padang for users of the UPT Library of Universitas Negeri Padang. This research method uses a quantitative type of research with a descriptive method. In this study, researchers used two research instruments, namely questionnaire and interview. The questionnaire adapted from Hidayat (2007). This questionnaire has 19 questions divided into four categories namely; frequency of Ebsco online database utilization, purpose of utilization of Ebsco online database, ability of users to browse collections and actions on information search results on Ebsco online databases. From 61 repondents, it can be concluded that users of the Ebsco online database are categorized as "frequent". Based on the results of the analysis using four categories, the results of the overall variables were obtained, there were 28 users with a percentage of 46% of the information retrieval process and information search results in the Ebsco online database.The aspect that influence the use of collections are the frequency of users, the purpose of users, the ability of users to trace collections and the role of librarians. From the results of this study, the frequency of utilization was the most influence aspect the activity in the utilization of the Ebsco online database with a frequency of 44% (in the category of sometimes). So the results of the study on the utilization of the Ebsco online database as a whole were found to be in the "frequent" category with a frequency of 28 and a percentage of 46%.